Generating bipolar magnetic fields by using unipolar power sources - Hernández, A.; Mazón, E.E.; Mena, E.; Cano, M.E. (Revista Mexicana de Física E, 2015)
A low cost current inversion system is presented as solution to achieve bipolar magnetic fields through a series array of analog programmable unipolar power sources. The system is based on a digital signal controller to provide an accurate zero-crossing detection of the voltage supplied to a commercial electromagnet, and a polarity inversion system composed of a set of switches in H-bridge configuration and optical isolators. Furthermore a stage of magnetic uncoupling is performed to generate a pair of independent signals to drive each power supply. In general the system have shown be able to generate fine and coarse magnetic field sweeps, which can be used to conduct studies of basic science or academic works in a physics laboratory, bypassing the absence of an expensive bipolar power source.